400 Years of Cultural Exchanges between China and Europe the History of the Grand Ricci Dictionary = 中歐文化交流400年《利氏漢法辭典》之溯源 (Ricci Institutes, 2006)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries

Cambridge Latin Course: Book I (Cambridge University Press, 2006)
The leading Latin course worldwide Book I begins in the city of Pompeii shortly before the eruption of Vesuvius. Book I is full colour throughout, with a clear layout of stories and language notes. Featuring a glossary for quick reference and comprehension questions, the book also includes a full explanation of language points and grammar practice exercises
OCLC: 729656629
Keywords: Civilization; Latin (Langue) Étude et enseignement (Secondaire); Latin language Study and teaching (Secondary); Rome (Empire); Rome Civilisation; Rome Civilization

Last Minute English HKCEE For 2007 New Syllabus: The Essentials of The New Syllabus 5* - Eng, Richard (Original Press (Asia) Ltd., 2006)

Hong Kong Indult Tridentine Latin Mass: Solemn High Mass = 香港主教特准特倫多拉丁文彌撒 - Gounod, Charles (Rosary Church & Diocesan Liturgy Commission, 2006)

中英應用文大全 = A comprehensive guide to modern Chinese and English practical writing - 沈, 達信; 鄧, 彥龍 (世界出版社, 2006)
OCLC: 1296161366
Keywords: Letter writing; Letter writing; Chinese